China's idiosyncratic economics: An emerging unknown monism driven by pluralism - Shuanping Dai (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2017)
China's economics education started at the beginning of the 20th century, when China was learning from the Western civilization, and accordingly economics curriculum system was introduced as well. As the communist government was established in 1949, economics education in China was interrupted, started to follow a conventional Marxism, and almost acted as ideological education approach and as a tool to economic plan. The fundamental economic reform from 1980s brought modern economics back to China, and from 1990s, economists who were educated in Europe and the USA introduced Western Economics, of which majority are neoliberalism, to China's Universities, and the popular economics textbooks and curriculum prevailed in China as well. This made the existing socialism economics education struggling in the research evaluation and classroom, although the Communist Party still is giving strong support to Marxism. The 2005 debate between Marxist and Neoliberalism actually reflected two monism tried to lead whole China's economics education. A hidden issue behind the learning from the West is that China's economists are keeping pursuing an approach based on China's reality, which in particular has been reinforced by the recent impressive economic success. Generally, China's economists have a common sense of that China did not follow a single economic theory to lead its reform and development, and believe that China's success can contribute to economics, although none tells what is a China's idiosyncratic economics. Hence, an unknown monism might be emerging in China, but pluralism may act as a channel for understanding Chinese economy, and accordingly be the essential parts of China's idiosyncrasy economics, which will be a new monism.
Keywords: 330; China's Idiosyncratic Economics; Pluralism in Economics Education; Monism; Marxian Political Economy